2021
DOI: 10.1051/matecconf/202133303007
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of Amorphous Silicon Nanoparticles Synthesized by Induction Thermal Plasma

Abstract: This study focus on the synthesis of amorphous silicon nanoparticles and understanding the formation mechanism. Counter-flow quenching gases with different flow rates were injected from downstream of the torch to understand the effect of quenching gas on the formation of silicon nanoparticles. Transmission electron microscopy show that nanoparticles with spherical shape and agglomerates consist of smaller particles were synthesized. X-ray diffraction analysis is used to calculate the amorphization degree, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…We reported a one-step formation method of carbon coated SiNPs with induction thermal plasma in a recent paper (Zhang et al, 2020). Induction thermal plasma is attractive to synthesize nanoparticles with high purity due to its advantages, such as high temperature (over 10 4 K), long residence time for precursors (several to hundreds of milliseconds), outstanding quenching e ect (10 3 -10 6 K/s), and electrodeless characterization (Tanaka et al, 2016;Zhang et al, 2021c). Previous studies already demonstrated the hydrocarbon decomposition processing and the subsequent surface reactions, which are in uenced by the ambient temperature of reaction chamber, can determine the formation of carbon coating as well as the coating properties (Zhang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…We reported a one-step formation method of carbon coated SiNPs with induction thermal plasma in a recent paper (Zhang et al, 2020). Induction thermal plasma is attractive to synthesize nanoparticles with high purity due to its advantages, such as high temperature (over 10 4 K), long residence time for precursors (several to hundreds of milliseconds), outstanding quenching e ect (10 3 -10 6 K/s), and electrodeless characterization (Tanaka et al, 2016;Zhang et al, 2021c). Previous studies already demonstrated the hydrocarbon decomposition processing and the subsequent surface reactions, which are in uenced by the ambient temperature of reaction chamber, can determine the formation of carbon coating as well as the coating properties (Zhang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%